Impacts of soil biosolarization with eggshell waste on soil health, microbial communities, and gas emissions - Li, Chunyu; Yu, Peirong; Zeng, Yuying; Qiu, Bixia; Chen, Mengfan; Cai, Danchun; Zhao, Zihui; Chen, Zhu’an; Yaron, Sima; Achmon, Yigal (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe global generation of large amounts of eggshell waste (ESW) is a persistent annual issue, requiring sustainable disposal solutions. Soil biosolarization (SBS), which combines organic amendments with solar heating, is a sustainable agricultural practice that serves as an alternative to chemical soil fumigation for effective pest control. This study evaluates the feasibility of using ESW as a soil amendment in SBS.MethodsA bioreactor-based simulation system was used to conduct SBS experiments under aerobic and anaerobic conditions. Assessments included soil health, microbial activity, soil microbiome, and phytotoxicity.Results and discussionThe results demonstrate that ESW significantly altered the pH of acidic soils, shifting them toward neutral and alkaline conditions. CO₂ emissions from ESW-amended soils increased in both aerobic (up to 7.0 mg CO₂/g soil) and anaerobic conditions (0.62 mg CO₂/g soil), indicating efficient microbial utilization of ESW and enhanced microbial activity. Additionally, ESW promoted the release of functional volatile organic compounds such as dimethyl sulfide, methanethiol, ammonia, and formic acid, which are known to suppress soilborne pathogens. Bacterial community analysis showed that ESW amendments promoted beneficial genera (e.g., Bacillus, Brevibacillus, Paenibacillus) associated with pest suppression and plant growth, while inhibiting harmful genera like Alicyclobacillus. Residual phytotoxicity on lettuce seedlings remained low, and weed seed inactivation of Bidens pilosa was effective in all SBS simulations with ESW.ConclusionThese findings highlight the potential of ESW to enhance SBS efficiency, suppress pathogens, and promote sustainable waste recycling.